Effects of metformin on proliferation and apoptosis of human megakaryoblastic Dami and MEG-01 cells - Xue Liang; Peiyan Kong; Jin Wang; Yulin Xu; Chunfang Gao; Guozhen Guo (Elsevier, 2017)
Metformin has received increasing attention for its potential anticancer activity against certain human leukemia cells, but its effects on human megakaryoblastic cells are unclear. This study aimed to investigate the effects of metformin on proliferation and apoptosis of human megakaryoblastic cells (Dami and MEG-01) and the underlying molecular mechanisms. CCK8 assay was employed to measure cell proliferation. Flow cytometry was adopted to detect cell apoptosis. Western blot was further employed to measure apoptosis-related proteins. In Dami and MEG-01 cells, metformin significantly inhibited proliferation and promoted apoptosis in a dose- and time-dependent manner, and metformin (4 mM) was selected for subsequent experiments. Metformin inhibited ERK1/2, JNK, and PI3K/Akt, but activated p38 pathway in these two cells. Moreover, inhibition of ERK1/2, JNK or PI3K/Akt pathway alone induced cell apoptosis compared to the control group. The combination of specific inhibitors of ERK1/2, JNK or PI3K/Akt pathway and metformin further promoted cell apoptosis and the up-regulation of p21, Bax, Bad, cleaved caspase-3 and -9 as well as the down-regulation of Bcl-2 mediated by metformin alone, but inhibition of p38 pathway exhibited the opposite results. These findings support the possibility of metformin treatment as a new therapeutic strategy against acute megakaryoblastic leukemia (AMKL).